2005
DOI: 10.1016/j.bbamem.2005.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Connexin-based gap junction hemichannels: Gating mechanisms

Abstract: Connexins (Cxs) form hemichannels and gap junction channels. Each gap junction channel is composed of two hemichannels, also termed connexons, one from each of the coupled cells. Hemichannels are hexamers assembled in the ER, the Golgi, or a post Golgi compartment. They are transported to the cell surface in vesicles and inserted by vesicle fusion, and then dock with a hemichannel in an apposed membrane to form a cell-cell channel. It was thought that hemichannels should remain closed until docking with anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
300
1
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(311 citation statements)
references
References 96 publications
(89 reference statements)
5
300
1
5
Order By: Relevance
“…An indirect effect of S. aureus on astrocyte Cx26 expression could be envisioned to occur through an autocrine/paracrine action since both TNF-α and IL-1β are capable of activating MAPK pathways upon binding to their cognate receptors (Hanada and Yoshimura, 2002). Since Cx26 is not phosphorylated it is more likely that any indirect effects of proinflammatory stimuli would be exerted at the level of transcription/ translation (Kojima et al, 1999;Saez et al, 1998Saez et al, , 2005Traub et al, 1989). Although Temme et al (1998) have reported that IL-1 and TNF-α augment Cx26 while decreasing Cx32 mRNA expression in hepatocytes, to our knowledge, the role of proinflammatory mediators on modulating Cx26 levels in astrocytes has not yet been examined.…”
Section: Discussionmentioning
confidence: 99%
“…An indirect effect of S. aureus on astrocyte Cx26 expression could be envisioned to occur through an autocrine/paracrine action since both TNF-α and IL-1β are capable of activating MAPK pathways upon binding to their cognate receptors (Hanada and Yoshimura, 2002). Since Cx26 is not phosphorylated it is more likely that any indirect effects of proinflammatory stimuli would be exerted at the level of transcription/ translation (Kojima et al, 1999;Saez et al, 1998Saez et al, , 2005Traub et al, 1989). Although Temme et al (1998) have reported that IL-1 and TNF-α augment Cx26 while decreasing Cx32 mRNA expression in hepatocytes, to our knowledge, the role of proinflammatory mediators on modulating Cx26 levels in astrocytes has not yet been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Because low calcium has been reported to activate connexin hemichannel activity (Sáez et al 2005), we examined the effect of removing calcium and magnesium from the bath solution. 15 cells expressing Cx31.3 and 6 control cells were examined in whole cell configuration with standard bath solution.…”
Section: Functional Properties Of Cx313mentioning
confidence: 99%
“…Other studies showed that leakage of cytosolic molecules and uptake of extracellular, membrane-impermeant tracers may be abolished by drugs or conditions blocking gap junction channels (Liu et al 1998;Hofer and Dermietzel 1998;Kondo et al 2000;Quist et al 2000). Finally, electrophysiology of single cells identified currents with voltage sensitivity and unitary conductances approximatively as expected for half junctional channels, made of unpaired connexons (Harris 2001;Stout et al 2004;Saez et al 2005;Spray et al 2006). Subsequently, however, the connexin hypothesis has been challenged by the evidence that proteins of the independent family of pannexins, discovered by Panchin et al (2000) and which do not form cell-to-cell channels, are prone to form the permeation pathway attributed to "hemichannels" (Bruzzone et al 2003;Bao et al 2004;Locovei et al 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…Because the channels made by connexins (Cx) at gap junction domains of the cell membrane are permeated by both ions and larger molecules (Harris 2001), it was initially surmised that connexin proteins could also form single, unpaired connexons on the nonjunctional cell membrane, thereby providing the structural basis for the "hemichannels" that would account for the membrane permeation by hydrophilic molecules (Goodenough and Paul 2003;Stout et al 2004;Saez et al 2005;Spray et al 2006). Consistent with this hypothesis, biochemical, immunolabeling, and expression studies revealed that connexons may be inserted in nonjunctional regions of the cell membrane (Musil et al 1991;Paul et al 1991;De Vries et al 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation